2020
DOI: 10.5137/1019-5149.jtn.30733-20.2
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality supported cervical transpedicular fixation on 3D-printed vertebrae model: an experimental education study

Abstract: AIM:To investigate the use of Augmented Reality (AR) technology as it contributes to spinal surgery education with the free-hand technique, and might reduce the error ratio. MATERIAL and METHODS:Ten candidates, with anatomy education but no surgical experience, applied 36 pedicle screws with C2-C3 posterior transpedicular fixation technique to nine vertebrae models produced via a three-dimensional (3D) printer. RESULTS:Using AR to apply pedicle screws to the experimental vertebrae model increased the safety sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Thirdly it was examined the methods applied in the studies, the variables and tools of statistical data analysis and the targeted study groups have represented the studies collocated examined had shown in the variables section that most studies focus on learning and performance and academic success achievement which is been measured like for example in a study by Celik et al (2020) the study focused on designing an application that is suitable for the laboratory training from teachers perspective that showed a positive effect on learning and the application future Potential on students laboratory learning about heart anatomical structure and the future teaching concepts and structure, in the tools section it showed that the most studies focused on data statistical tools that based mostly on experimental measurement the evaluative data recommends a few positive effects of AR application on student learning, for example in a study by Boyaci and Aslan (2020). Also, Fokides and Mastrokoukou (2018) in those studies the data statistical tools that are used were pre-test and post-test and showed that 3D models designed in those studies may well be a supportive instructive fabric, the study groups differed from students in different levels of education levels were from primary students, high school students, and middle school students and college students and other professionals specialized in health education and medical studies wither teachers and physicians and nursing specialized and that focus was applied to show where the technology was applied is more effective and which study group has shown more positive response and easy adaptation of this innovation.…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly it was examined the methods applied in the studies, the variables and tools of statistical data analysis and the targeted study groups have represented the studies collocated examined had shown in the variables section that most studies focus on learning and performance and academic success achievement which is been measured like for example in a study by Celik et al (2020) the study focused on designing an application that is suitable for the laboratory training from teachers perspective that showed a positive effect on learning and the application future Potential on students laboratory learning about heart anatomical structure and the future teaching concepts and structure, in the tools section it showed that the most studies focused on data statistical tools that based mostly on experimental measurement the evaluative data recommends a few positive effects of AR application on student learning, for example in a study by Boyaci and Aslan (2020). Also, Fokides and Mastrokoukou (2018) in those studies the data statistical tools that are used were pre-test and post-test and showed that 3D models designed in those studies may well be a supportive instructive fabric, the study groups differed from students in different levels of education levels were from primary students, high school students, and middle school students and college students and other professionals specialized in health education and medical studies wither teachers and physicians and nursing specialized and that focus was applied to show where the technology was applied is more effective and which study group has shown more positive response and easy adaptation of this innovation.…”
Section: Resultsmentioning
confidence: 99%
“…Description and Study Display of educational content in relevant locations [56], [60], [86] Information [45], [54] [95] Presentation of ideal behavior [64], [66], [67], [84] [69], [78] Demonstration [61], [63], [88] [91] Expanding the flexibility of training content by adding information to physical objects [38], [39], [41], [46], [80] [68], [69], [70], [75] [92] Facilitation of the skill transfer through imitation of the actual [14], [42], [43], [44], [45] Task support by presenting relevant information [16], [36], [41], [47], [49], [50], [51], [53] Practice [86], [87] [83] Feedback on the performance, problems, and ways to improve [39] [59] [65] Real-time feedback for motion compensation [71], [72], [75], [76], [78], [82] [41] Real-time visualization of invisible current conditions Feedback [93] learning prin...…”
Section: Strategymentioning
confidence: 99%
“…For example, scanning significantly increased (from 16% to 27%), accounting for a quarter of the research in professional training. In this way, AR devices were equipped with a camera or webcam to scan the QR code to help students to acquire instructional content, such as texts, images, and videos [30,31]. Another artificial type, inputting by mouse and keyboard, also showed an increase since 2016 (from 5% to 12%).…”
Section: Input and Outputmentioning
confidence: 99%